Effect of Microcurrent Electrical Therapy on Healing of Excisional Skin Wounds - Polat, Eren; Karademir, Kadir; Cevik, Havva Nur; Bazar, Ceyda; Kaya, Emre; Ozoner, Ozgur; Ozoner, Merve Pekince (Univ Cordoba, 2025)
Objective. Many applications and pharmaceutical active substances have been used since the beginning of human history to ensure healthy and rapid healing of wounds. This study aimed to determine the effectiveness of microcurrent electrical therapy on wound healing. Material and methods. A full-thickness sectional skin wound of 4 cm2 in size was created in the interscapular region of the 14 rabbits used in the study. Microcurrent electrotherapy was applied to rabbits with excisional skin wounds for 10 days. Results. At the end of the 10th day, when the wound closure rates were compared, it was determined that the rabbits in the microcurrent electrotherapy (ME) group were in better condition than the rabbits in the control group (CG). In the histopathological scoring, it was determined that there was no statistical difference between the two groups (p>0.05). When evaluated biochemically, MDA levels of rabbits in the ME group were determined to be statistically significantly higher. GSH, CAT, GSH-Px levels were found to be statistically significantly lower in rabbits in the ME group (p<0.001). Conclusions. As a result, according to the findings from this study, it was determined that microcurrent electrotherapy application clinically accelerated wound healing. However, due to the short study period, no histopathological difference could be detected between the groups in wound healing.
Keywords: Electrotherapy; healing; microcurrent; wound ( Source: NLM )